Public investment management efficiency in the argentine provinces - Capello, Marcelo Luis (Inter-American Development Bank, 2024)
Fil: Capello, Marcelo Luis. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas; Argentina.